Education and New Developments 2022 – Volume 2 2022
DOI: 10.36315/2022v2end018
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation Techniques and Tools for Online Project-Based Learning With Primary School Students

Abstract: "Current trends indicate that more schooling will take place online, including project-based learning (PBL). This shift opens new possibilities for interactions and collaborations among students, allowing for glocalization of learning and connectivism across international classrooms. The last two years have shown that many well-established techniques/tools for facilitating PBL in physical classrooms are not simply transferable to the online space. Thus, techniques/tools for online facilitation need to be explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…As noted previously "Section 4.1", this is problematic from a research perspective, with educational technology research often being criticised for lacking theoretical foundations (Hew et al, 2019). Technologies, as well as utilized teaching and facilitation techniques in online and technology-enhanced learning environments should be anchored in relevant educational (and psychological) theories and empirical research (Goagoses et al, 2022). Lastly, we found that more than half of the included studies, authors did not systematically report and/or assess utilized technologies (hardware and software).…”
Section: Limitations Of the Included Studiesmentioning
confidence: 99%
“…As noted previously "Section 4.1", this is problematic from a research perspective, with educational technology research often being criticised for lacking theoretical foundations (Hew et al, 2019). Technologies, as well as utilized teaching and facilitation techniques in online and technology-enhanced learning environments should be anchored in relevant educational (and psychological) theories and empirical research (Goagoses et al, 2022). Lastly, we found that more than half of the included studies, authors did not systematically report and/or assess utilized technologies (hardware and software).…”
Section: Limitations Of the Included Studiesmentioning
confidence: 99%
“…In a blended learning environment, students typically engage in a mix of in-person classroom sessions and online activities [2]. The face-to-face component allows for direct interaction with teachers and peers, fostering a collaborative and social learning environment [3]. This interaction is valuable for discussions, group activities, and hands-on experiences that may be challenging to replicate in a purely online setting.…”
Section: Introduction Of Blended Learningmentioning
confidence: 99%
“…All participating children expressed the need for facilitation, yet individual children commented on the experienced differences of communication behaviours, such as non responsiveness, as well as the pace of design activities being too slow for some and challenging for others [9]. Reflecting on these observations, in the subsequent project, we introduced tailor made ice-breakers in an attempt to bring all participants in the same "rhythm" while also developing strategies and tools with the children to solve identified online communication challenges [4,12].…”
Section: Introductionmentioning
confidence: 99%